A Green Clustering Protocol for Mobile Sensor Network Using Particle Swarm Optimization - ., Nurul Mu’azzah Abdul Latiff NikNoordini, NikAbdMalik Abdul Halim (2016)
Energy consumption of sensor nodes is one of the crucial issues in prolonging the lifetime of wireless sensor networks. One of the methods that can improve the utilization of sensor nodes batteries is the clustering method. In this paper, we propose a green clustering protocol for mobile sensor networks using particle swarm optimization (PSO) algorithm.